(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
Achieving food security and independence involves overcoming various risks and threats. The most probable and dangerous risks should be recognized: natural, weather and man-made; economic and industrial; innovative. Macroeconomic risks, including those related to the global market situation, as well as political risks of a national and global scale, have a strong impact on the agri-food complex. The most important aspects of food security are considered, the main criteria and measures for the formation of effective mechanisms for ensuring food security in the context of globalization.